2013
DOI: 10.1021/am401961s
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystals of 10-Methylphenthiazine and 1,3-Dinitrobenzene: Implications for the Optical Sensing of TNT-Based Explosives

Abstract: The evaporation of an ethanol solution containing an equimolar mixture of 10-methylphenothiazine and 1,3-dinitrobenzene gave red-purple crystals. The diffuse reflection spectrum for the cocrystals showed a low reflectance from the UV through the visible spectrum until the reflectance increased at the red end of the visible spectrum. The crystal structure showed alternating π stacking of the electron-rich 10-methylphenothiazine and the electron-poor 1,3-dinitrobenzene. There were also hydrogen bonding interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Fluorescence properties of organic compounds rely not only on the structure of the fluorophore but also on the architecture of crystal packing and simultaneously on the nature and strength of intermolecular interactions . Organic compounds with molecular-packing-directed luminescence , have gained significant popularity and attention due to their remarkable properties and promising optoelectronic applications in the fields of lasers, sensors, organic light-emitting diodes,and optical data storage . Numerous strategies have been employed to acquire tunable luminescent materials, since traditional structure tailoring techniques on single molecular materials have accomplished restricted success.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence properties of organic compounds rely not only on the structure of the fluorophore but also on the architecture of crystal packing and simultaneously on the nature and strength of intermolecular interactions . Organic compounds with molecular-packing-directed luminescence , have gained significant popularity and attention due to their remarkable properties and promising optoelectronic applications in the fields of lasers, sensors, organic light-emitting diodes,and optical data storage . Numerous strategies have been employed to acquire tunable luminescent materials, since traditional structure tailoring techniques on single molecular materials have accomplished restricted success.…”
Section: Introductionmentioning
confidence: 99%
“…It has been generally found that π-conjugated organic molecules consisting of electron-donating or -withdrawing substituents have the usual propensity to co-crystallize through π–π stacking interactions in two different packing motifs, namely, segregated stacking , and mixed stacking . In the segregated stacking mode, the π-electron-rich (A) and π-electron-deficient (B) molecules form separate π-stacked columns (A–A–A–A, B–B–B–B), whereas in the mixed stacking mode, the constituent molecules are alternately arranged over each other along the π-stacking column (A–B–A–B).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Several methods are used to detect those explosives like surface plasma resonance, field effect transition, portable mass spectrometry, ion mobility spectrometry, Xray systems, electrochemical methods, microcantilever and optical based sensing. [3][4][5][6][7] Among them, fluorescence based optical sensing is one of the finest techniques to detect those nitro explosives and become very popular because of its simple instrumentation, cost-efficiency, fast and high sensitivity. 8,9 Generally, nitro-aromatic derivatives are being used world-wide to prepare different explosives.…”
mentioning
confidence: 99%
“…Our group and others have reported recently the significance and ability of luminescent coordination polymers , and metal organic frameworks in the detection of nitro-aromatics. It is known that the nitro-aromatics are electron-deficient compounds and able to form colored CT complexes with electron-rich compounds. , However, the excited state behavior, in particular, the ISC between singlet and triplet state of CT cocrystals, formed by the combination of nitro-aromatics and electron rich compounds is limited in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the nitro-aromatics are electron-deficient compounds and able to form colored CT complexes with electron-rich compounds. 33,34 However, the excited state behavior, in particular, the ISC between singlet and triplet state of CT cocrystals, formed by the combination of nitro-aromatics and electron rich compounds is limited in the literature.…”
Section: ■ Introductionmentioning
confidence: 99%